2007
DOI: 10.1177/0146167207305540
|View full text |Cite
|
Sign up to set email alerts
|

From the Interpersonal to the International: Understanding Commitment to the “War on Terror”

Abstract: Applying constructs from the investment model used traditionally to understand interpersonal commitment, the present investigation seeks to elucidate social cognitive antecedents of commitment to the war on terror waged by the United States. In Study 1, satisfaction with, investments in, and alternatives to the war on terror predict levels of commitment to the war beyond several important control variables. In Study 2, levels of satisfaction with, investments in, and alternatives to the war are experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…This view fits well with findings that conservatives support governmental military spending to a greater extent than liberals, presumably because the military may protect against potential future threats (Pratto, Sidanius, Stallworth, & Malle, 1994). Further corroborating this view, political conservatism has been associated with greater support for war (Agnew, Hoffman, Lehmiller, & Duncan, 2007;Grote, Frieze, & Schmidt, 1997), and this result extends to support for the current war in Iraq. Compared to liberals, conservatives were more in favor of military action to end Saddam Hussein's rule before the war started, and they were more likely to continue to think that the war was the right decision after public opinion started to turn (e.g., World Public Opinion, 2006).…”
Section: Political Orientation Support For War and Attribution Stylessupporting
confidence: 81%
“…This view fits well with findings that conservatives support governmental military spending to a greater extent than liberals, presumably because the military may protect against potential future threats (Pratto, Sidanius, Stallworth, & Malle, 1994). Further corroborating this view, political conservatism has been associated with greater support for war (Agnew, Hoffman, Lehmiller, & Duncan, 2007;Grote, Frieze, & Schmidt, 1997), and this result extends to support for the current war in Iraq. Compared to liberals, conservatives were more in favor of military action to end Saddam Hussein's rule before the war started, and they were more likely to continue to think that the war was the right decision after public opinion started to turn (e.g., World Public Opinion, 2006).…”
Section: Political Orientation Support For War and Attribution Stylessupporting
confidence: 81%
“…By contrast, the investment model would predict that people use specific policy performance criteria to determine the value of persisting with the same policy. Agnew and colleagues (Agnew, Hoffman, Lehmiller, & Duncan, 2007) used the investment model to examine commitment to the "war on terror" waged by the United States under President George W. Bush. They conducted two experiments in which they simultaneously manipulated the three investment model constructs (a novel aspect of this research).…”
Section: Recent Applications Of the Investment Modelmentioning
confidence: 99%
“…Some studies (Agnew, Hoffman, Lehmiller, & Duncan, 2007;Federico, Golec, & Dial, 2005) have underlined the role of psychological reaction to terrorism in understanding public support for government antiterrorist policies. These studies have shown that terrorist events -when defined as being serious threats to national security -usually promote support for military actions.…”
Section: Terrorism and The War On Terrorismmentioning
confidence: 99%